Experimental training of pre-service teachers to assess content in integrated listening-into-writing - Юлія Лавренчук (Ars Linguodidacticae)
As part of a broader investigation into pre-service teachers' assessment literacy, this paper focuses on training undergraduates to assess content in integrated listening-into-writing. The article emphasises the importance of analysing the content of students' writing separately from other criteria, in particular, language accuracy. Grounded on the constructivist and action-oriented approaches to acquiring knowledge and skills, the findings and propositions are presented as scaffolded training activities. The experimental training sessions were conducted as workshops for 3rd-year students (n = 25) within the Testing and Assessment course at Taras Shevchenko National University of Kyiv. The improved quality of students' reflections on the ILW samples they assessed during the workshop reflected the positive outcome. The paper summarises the experience and outlines pedagogical challenges, learning outcomes, and potential opportunities in higher educ